Pengaruh Strategi Bisnis dan Corporate Social Responsibility terhadap Tax Avoidance dengan Kinerja Laba Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Jasa Properti, Real Estate dan Konstruksi Bangunan yang Terdaftar di BEI Periode 2015-2019) - Elinda Ritnawati; eva herianti (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2021)
The research aims to analyze the effect of Business Strategy and Corporate Social Responsibility against Tax Avoidance with Earnings Performance Variabel as a moderating variabel. The research is a quantitative study using secondary data in the form of Annual Report of Service Company sektor property, Real Estate, and Building Construction listed on the Indonesia Stock Exchangne (IDX) in 2015-2019. In this research the process of sampling uses purposive sampling with criteria determined by the research. Then produced 27 Service Company sektor property, Real Estate, and Building Construction. The data analysis technique used is multiple linear regression analysis using E-views version 10 as a data analysis tool. The result of this research indicate that Business Strategy have no significant effect on Tax Avoidance with probability value of 0.754 and Earning Performance moderating Business Strategy have no significant effect on Tax Avoidance with probability value of 0.487. Meanwhile Corporate Social Responsbility have a significant effect on Tax Avoidance with probability value of 0.000 and Earning Perfomance strengthen the Corprate Social responsibility on Tax Avoidance wuth probability value of 0.005.